SIKAVALTA: A responsive webGIS-based calculator for prescriptive economic valuation of agricultural land losses caused by pests and hydrometeorological disasters in East Luwu - Rusmala; Abdullah Syukur; Fahrul Basir; Arsita Eka Oktaviani; Ichwan Muis; Andi Jumardi (CV. Literasi Indonesia, 2026)
East Luwu Regency is a strategic food-producing area that increasingly faces a double exposure to crop-pest infestations and hydrometeorological disasters such as flooding. Until now, the assessment of post-disaster economic losses in the region has leaned on manual recapitulation, a method that is slow, prone to human error, and unable to capture the spatial variability between land parcels. The resulting delay holds up the disbursement of government relief and rice-farming insurance claims, which weakens the capital resilience of smallholders. This study develops SIKAVALTA, a responsive web-based geographic information system that converts physical crop damage from biotic and abiotic hazards into a monetary value expressed in Rupiah. The system was built through a Research and Development approach using the JITU method, namely Data Netting, Formula Interpretation, Web Technology, and Validity Testing. The prototype integrates on-map land digitization, automatic geodesic area computation, a deterministic valuation engine for rice and oil-palm commodities, and report export in document and spreadsheet formats. Black-Box testing confirmed that every feature operated as intended, and the user-acceptance evaluation cleared the minimum feasibility threshold. SIKAVALTA therefore shows a prescriptive spatial valuation capability that sets it apart from conventional descriptive mapping systems.